Assessing The Utility Of Swayam Diabetes Mobile Health Application For Self-Care Management Of Type 2 Diabetes In Home Settings - P Sinha, Abhijeet; Singhal, Manmohan; Joshi, Ashish; Kumar, Rohitashwa (Journal of Neonatal Surgery, 2025)
Background: The prevalence of type 2 diabetes mellitus (T2DM) is increasing at an alarming rate, presenting a significant public health challenge both nationally and globally. The Swayam Diabetes mobile health (mHealth) application was developed and tested to support self-care management of T2DM in home settings. The application incorporates key features such as self-monitoring tools, a daily diary, educational resources, and user support, all designed to facilitate effective self-care management of T2DM in urban home environments. Materials and methods: A mixed-methods research design was employed, combining both qualitative and quantitative approaches. The Swayam Diabetes mobile application was developed based on pretesting conducted with 18 users. Following this, user testing was carried out with 250 participants who completed a Diabetes Management Survey (DBMS). A follow-up assessment was conducted over six months with 55 users to evaluate the application’s utility and gather feedback, using the System Usability Scale (SUS) for usability assessment. Results: Seventy-eight percent of users preferred using the Swayam Diabetes mobile application to monitor their daily self-care activities, including food intake, nutrition, physical activity, medication adherence, and other diabetes-related information. The study observed a 5.1% improvement in self-care management, with over 55% of participants utilizing the daily diary feature. Participants reported that self-management through the mobile health application was beneficial. However, the study found minimal impact of gender on self-care outcomes. Conclusion: The Mobile application enabled users to effectively monitor key health aspects such as nutrition, activity, and medication adherence. High user engagement, particularly with the daily diary feature, highlights its value in self-care management. Future research should focus on the long-term impact on clinical outcomes, like HbA1c levels, and assess its effectiveness across diverse populations.